Scenic automation handbook - Conner, Gareth (Routledge, 2018)
Scenic automation has earned a reputation of being complicated and cantankerous, a craft best left to the elite of our industry. Not sure of the difference between a VFD, PLC, or PID? If you have dreamed of choreographing scene changes with computerized machinery, but get lost in the technical jargon the Scenic Automation Handbook will guide you along the road to elegant automation. Adopting a pragmatic approach, this book breaks down any automation system into five points, known as the Pentagon of Power. Breaking down a dauntingly complex system into bite- size pieces makes it easy to understand how components function, connect, and communicate to form a complete system. Presenting the fundamental behaviors and functions of Machinery, Feedback Sensors, Amplifiers, Controls, and Operator Interfaces, the Scenic Automation Handbook demystifies automation, reinforcing each concept with practical examples that can be used for experimentation. Automation is accessible - come along and learn how!